Kepatuhan Syariah dalam Penerbitan Sukuk: Pendekatan Kualitatif Berbasis Fatwa DSN-MUI dan Peraturan OJK di Indonesia - Ardiansah, Muhamad Resa; Hidayah, Nur; Muhajirin, Muhajirin (Yayasan Riset dan Pengembangan Intelektual, 2026)
Objective: This study aims to describe the elements of sharia compliance contained in sukuk, based on the fatwas of the National Sharia Council (DSN-MUI) and several regulations issued by the Financial Services Authority (OJK) in Indonesia. Design/Methodology/Approach: This study uses a qualitative approach with documentary and secondary data, including fatwas and regulations required to explore the sharia compliance of sukuk. This study highlights and identifies the elements of sharia compliance using a hierarchy map. Findings: Sukuk in Indonesia fulfills sharia compliance through: (1) absolute prohibition of riba, gharar, maysir, tadlis, dharar, risywah, zhulm, and haram activities; (2) halal underlying assets (tangible assets, asset benefits, services, certain projects, or certain investment activities) with a minimum of 51 percent tangible assets for traded sukuk; (3) transparent returns in the form of profit sharing, margins, or ujrah in accordance with sharia contracts (mudharabah, musyarakah, ijarah, wakalah, murabahah, salam, istishna'); (4) implementation of maqasid sharia through the principle of